Microbial Exopolysaccharides: From Genes to Applications - Jochen Schmid (Frontiers Research Topics, 2016)
Microbial polysaccharides represent an attractive alternative to those from plants or macro algae. They can be produced from renewable sources including lignocellulosic waste streams. Their production does not depend on geographical constraints and/or seasonal limitations. Additionally the manipulation of biosynthetic pathways to enhance productivity or to influence the chemi-cal polysaccharide composition is comparatively easy in bacteria. Microbial exopolysaccharides represents a valuable resource of biogenic and biodegradable polymers, suitable to replace petro based polymers in various technical applications. Furthermore, biocompatible exopolysaccha-rides are very attractive in medical applications, such as drug delivery systems, use as vaccines or nanoparticles. This research topic will depict the status quo, as well as the future needs in the field of EPS and biofilm research. Starting from the unexplored diversity of microbial polysaccharide producers to production processes and possibilities for modifications, to enhance the already high number of functionalities based on the chemical structures. An overview of the recent and future applications will be given, and the necessity in unravelling the biosynthesis of microbial exopolysaccharide producers is depicted, highlighting the future trend of tailor made polymers. Constraints in structure analysis of these highly complex biogenic polymers are described and different approaches to solve the restrictions in imaging and NMR analysis will be given. Therefore; this research topic comprises the whole process from genes to applications.